2007
DOI: 10.1196/annals.1411.005
|View full text |Cite
|
Sign up to set email alerts
|

ETV5 Is Required for Continuous Spermatogenesis in Adult Mice and May Mediate Blood–Testes Barrier Function and Testicular Immune Privilege

Abstract: The transcription factor Ets-variant gene 5 (ETV5) is essential for spermatogonial stem cell (SSC) self-renewal, as the targeted deletion of the Etv5 gene in mice (Etv5(-/-)) results in only the first wave of spermatogenesis. Reciprocal transplants of neonatal germ cells from wild-type (WT) and Etv5(-/-) testes were performed to determine the role of ETV5 in Sertoli cells and germ cells. ETV5 appears to be needed in both cell types for normal spermatogenesis. In addition, Etv5(-/-) recipients displayed increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 19 publications
0
36
0
Order By: Relevance
“…Mice with a targeted Etv5 deletion undergo the first wave of spermatogenesis, but they subsequently show progressive germ cell depletion and a Sertoli cell-only syndrome (Chen et al, 2005). Whether the defect was caused by Sertoli or germ cell dysfunction was unclear in the initial study, but germ cell transplantation experiments later showed that Etv5 is important in both germ cells and Sertoli cells and that Etv5-deficient SSCs have a limited ability to colonize seminiferous tubules of wild-type mice (Morrow et al, 2007;Tyage et al, 2009). By contrast, Bcl6b is not expressed in Sertoli cells, and the involvement of this gene in SSCs was discovered by microarray analyses of cultured spermatogonia stimulated with GDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Mice with a targeted Etv5 deletion undergo the first wave of spermatogenesis, but they subsequently show progressive germ cell depletion and a Sertoli cell-only syndrome (Chen et al, 2005). Whether the defect was caused by Sertoli or germ cell dysfunction was unclear in the initial study, but germ cell transplantation experiments later showed that Etv5 is important in both germ cells and Sertoli cells and that Etv5-deficient SSCs have a limited ability to colonize seminiferous tubules of wild-type mice (Morrow et al, 2007;Tyage et al, 2009). By contrast, Bcl6b is not expressed in Sertoli cells, and the involvement of this gene in SSCs was discovered by microarray analyses of cultured spermatogonia stimulated with GDNF.…”
Section: Discussionmentioning
confidence: 99%
“…ERM may be needed for maintenance of the blood-testis barrier and testicular immune privilege (Morrow et al, 2007). During postnatal development, spermatogonial loss in Erm 2/2 mice occurs between 4 and 8 days of age and is dramatic by 28 days.…”
Section: Spermatogonia and Their Dependencementioning
confidence: 99%
“…Studies using reciprocal transplantation of neonatal germ cells from wild-type and Etv5 À/À testes into W/W v recipient testes showed that ETV5 expression in neonatal germ cells is required for the initial establishment of the SSC pool and for homeostasis of SSC self-renewal and differentiation (19). ETV5 expression in Sertoli cells is critical for maintaining normal spermatogenesis (19).…”
mentioning
confidence: 99%